Primary localized amyloidosis in nasopharynx: a case report - Naserrudin, Nadia Syafeera; Ainer, Indumathi; Liew, Kong Yew; Ishak, Azlan Iskandar; Gnanasegaram, Hemlata Kumari (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Nasopharyngeal amyloidosis is an extremely rare benign tumour. It is divided into localized or systemic amyloidosis. It is more common in men. Clinical presentation includes nasal blockage, epistaxis and reduced hearing. Classical positive Congo red stain and appearance of apple green birefringence on polarized microscopy confirms the diagnosis of amyloidosis. We present a case of nasopharyngeal amyloidosis in a 44-year old lady who presented with acute hearing loss for 1 week with epistaxis mimicking nasopharyngeal carcinoma. Clinical examination showed a nasopharyngeal mass with biopsy proven AA amyloidosis. She is now cured of amyloidosis following endoscopic transnasal excision of tumour. We discuss on the similarity of presentation between nasopharyngeal carcinoma; the commonest malignant tumour in our region and the much rarer nasopharyngeal amyloidosis as well as highlighting the importance in early recognition of the latter in view of its known risk of systemic involvement.